PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI PECAHAN KELAS IV DI MIS MUHAMMADIYAH 2 SINGKAWANG - Nira; Rosmaiyadi, Abd.Basith (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand whether there is an influence on the understanding of the concept of grade IV students who use the contextual teaching and learning model at MIS Muhammadiyah 2 Singkawang. The type of research used is Quantitative with a Pre Experiment research design in the form of one group pretest- posttest design. The population in this study were all grade IV students of MIS Muhammadiyah 2 Singkawang and the sample was taken using the total sampling technique, namely all grade IV students totaling 22 students. The data collection technique and instrument used is the measurement technique. The data collection instrument used is a test sheet, the data analysis technique used is a two-sample paired t-test, Effect size, and N-gain. The results of the study show that. 1) The two- sample paired t-test showed 15,000> 0.05, so it can be concluded that there is an influence on the understanding of the concept of grade IV students who use the contextual teaching and learning model at MIS Muhammadiyah 2 Singkawang. 2) The test of the magnitude of the influence (effect size) of the contextual teaching and learning model on students' conceptual understanding, the result is that it is very influential with the result, the effect size is in the very large criteria with a value of 1.97 at about ES> 0.05. The implications of this study indicate that there is a need for a learning model, contextual teaching and learning has a positive impact on students' conceptual understanding, especially on fractional material. 3) The N-Gain test of this study aims to determine whether there is an increase before and after, the contextual teaching and learning model was taught at MIS Muhammadiyah 2 Singkawang with a value of 0.40 which is in the moderate criteria.